Pengaruh Kompetensi, Partisipasi Masyarakat, dan Pemanfaatan Teknologi Informasi Terhadap Akuntabilitas Pengelolaan Dana Desa - Ni Kadek Deviyanti; Ni Wayan Alit Erlina Wati (UNHI Press, 2022)
In view of this, this research was written todetermine the efect ofcompetence, community participations, and the use of informations technology onvillage fund managemet accountability.The population used in this study was 328 people who worked as village officials in 15 villages in Mengwi District. The sample used was 120 people who were determine using nonprobability sampling metod using purposive sampling technique and tested using multiple linear regresion analysis technique.The results of this study indicate that Competence has a positive and significant efect on the Vilage Fund Managemen Accountablity variable. Comunity participations has a positif and significan effect on Vilage Fund Managemnt Acuntability. Utilizations of Informations Tecnology has a positie and significan efect on Village Fund Management Accountabiliy. The result of this studi canbe used as considerations in designing regulation and policie relate tothe managemet of vilge funds.